Strengthening the Disaster Resilience of Indonesian Cities : A Policy Note - World Bank (World Bank, Washington, DC, 2019)
This note was prepared by World Bank staff and consultants as input into the Bank’s Indonesia Urbanization Flagship report, Time to ACT: Realizing Indonesia’s Urban Potential. The World Bank team was led by Jolanta Kryspin-Watson, Lead Disaster Risk Management Specialist, Jian Vun, Infrastructure Specialist, Zuzana Stanton-Geddes, Disaster Risk Management Specialist, and Gian Sandosh Semadeni, Disaster Risk Management Consultant. The paper was peer reviewed by World Bank staff including Alanna Simpson, Senior Disaster Risk Management Specialist, Abigail Baca, Senior Financial Officer, and Brenden Jongman, Young Professional. The background work, including technical analysis of flood risk, for this report received financial support from the Swiss State Secretariat for Economic Affairs (SECO) through the World Bank Indonesia Sustainable Urbanization (IDSUN) Multi-Donor Trust Fund. The findings, interpretations, and conclusions expressed do not necessarily reflect the views of the World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work.